2012
DOI: 10.1111/j.1474-9726.2012.00795.x
|View full text |Cite
|
Sign up to set email alerts
|

A senescent cell bystander effect: senescence‐induced senescence

Abstract: SummarySenescent cells produce and secrete various bioactive molecules including interleukins, growth factors, matrix-degrading enzymes and reactive oxygen species (ROS). Thus, it has been proposed that senescent cells can damage their local environment, and a stimulatory effect on tumour cell growth and invasiveness has been documented. However, it was unknown what effect, if any, senescent cells have on their normal, proliferation-competent counterparts. We show here that senescent cells induce a DNA damage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
506
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 600 publications
(525 citation statements)
references
References 21 publications
18
506
0
1
Order By: Relevance
“…While the formation of myofibroblasts during wound healing in a mouse model system was reported to be stimulated by SASP factors secreted from senescent fibroblasts and endothelial cells generated at the site of injury (Demaria et al, 2014), other studies demonstrated that, paradoxically, the SASP causes bystander senescence in somatic human fibroblasts (Acosta et al, 2013; Hubackova et al, 2012; Nelson et al, 2012). Recent studies, however, have raised the possibility that the SASP can promote development of myofibroblasts, as fibroblast incubated with conditioned medium from senescent cells develop into contractile α‐SMA‐expressing cells (Schafer et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While the formation of myofibroblasts during wound healing in a mouse model system was reported to be stimulated by SASP factors secreted from senescent fibroblasts and endothelial cells generated at the site of injury (Demaria et al, 2014), other studies demonstrated that, paradoxically, the SASP causes bystander senescence in somatic human fibroblasts (Acosta et al, 2013; Hubackova et al, 2012; Nelson et al, 2012). Recent studies, however, have raised the possibility that the SASP can promote development of myofibroblasts, as fibroblast incubated with conditioned medium from senescent cells develop into contractile α‐SMA‐expressing cells (Schafer et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, conditioned medium from senescent fibroblasts, as well as a number of molecules contained within this secretome including TGF‐β1 and IL1, can cause cellular senescence in neighboring fibroblasts through paracrine mechanisms (Acosta et al, 2013; Hubackova et al, 2012; Nelson et al, 2012). This bystander senescence is a consequence of cytokine‐mediated production of reactive oxygen species (ROS), which ultimately cause the formation of DSBs and activation of a persistent DDR in neighboring cells (Hubackova et al, 2012; Nelson et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…100,114 Paracrine geroconversion also takes place. 115,116 Gradually geroconversion involves most cells in diverse tissues. The extend of geroconversion can range from slightly gerogenic to typically senescent cells.…”
Section: From Gerontology To Medicinementioning
confidence: 99%
“…As a result, increased cellular senescence in bone marrow can be induced by cellular damage or environment changes. It is reported that senescent cells (SnCs) accumulate in bone marrow with aging (Farr et al., 2017) and contribute to age‐related pathologies through their secretion of factors contributing to the senescence‐associated secretory phenotype (SASP) (Campisi, 2000, 2013; Nelson et al., 2012). SnCs exhibit essentially stable cell cycle arrest through the actions of tumour suppressors such as p16 INK4a , p53, p21 CIP1 (Campisi, 2005; Serrano, Lin, McCurrach, Beach, & Lowe, 1997) and also include increased lysosomal β‐galactosidase activity, robust secretion of inflammatory cytokines/chemokines, and nuclear foci containing DNA damage response proteins or distinctive heterochromatin.…”
Section: Introductionmentioning
confidence: 99%